The effect of strain rate on macrozones of the α+β phase region during thermal deformation in near-α titanium alloys - Xiaolei Wang; Mengjia Wang; Peihao Ye; Wujing Fu; Guojian Cao; Qihang Han; Xuewen Li; Hao Wu; Guohua Fan (Journal of Materials Research and Technology)
The homogenous microstructure of near-a titanium alloys is important to service in complex and dynamic environments. However, macrozones characterized by sharp local textures are common microstructural inhomogeneities in titanium (Ti) alloys, which significantly reduce the fatigue resistance of Ti alloy components. In this study, the mechanism of macrozones formation and evolution were investigated. These results show that the β matrix is strengthened by the internal lamellar second α(αS) grains in the α+β phase region during thermal deformation. The strengthening effect dependent on the crystallographic orientation of the α grains. The random orientation of the αs grains leads to the formation of deformation-affected zones among these β grains, resulting in uneven deformation. In regions of the β grains with insufficient deformation, the αs grains acquire unenough energy for complete globularization, which results in the alignment of the αs grains with similar crystallographic orientations facilitating the formation of macrozones. At the strain rate of 10s−1, the β grains exhibit high resistance to deformation due to the presence of numerous thin α grains formed. In contrast, at the strain rate of 1s−1, the wider α grains appear within the β grains, leading to the lower deformation resistance and reduced macrozones formation. With the strain rate decreases, the interaction between adjacent grains is suppressed, then, inhibiting the formation of macrozones. This study is significance for understanding the effect of strain rates on macrozones formation and provides a fundamental basis for controlling macrozone formation in near-α titanium alloys.